Optical Properties Evaluation of CuIn1-xGaxSe2 Thin Films Using OPAL2 Calculator - Kouhlane, Yacine; Bouhafs, Djoudi; Nwadiaru, Ogechi-Vivian; Demagh, Nacer-Eddine; Chibani, Allaoua (Journal of Sustainable Materials Processing and Management, 2022)
OPAL2 calculator has proved to be an effective technique for simulating optical losses in various materials for various applications. This study demonstrates the use of this software to simulate the transmittance (T) and reflectance (R) and hence evaluate the optical properties of flash evaporated CuIn1-xGaxSe2 (CIGS) thin films with a ratio x = 0.28 deposited on stainless-steel (STS) and glass substrates. The simulation results exhibit excellent accuracy of the modeled design presented in this work. The CIGS with a ratio of gallium x = 0.3 showed the best matching between simulated and experimental T and R patterns. Moreover, the simulation shows that an increase in the gallium concentration increases optical losses. Finally, the results demonstrate the application of the freeware program OPAL2 to practically simulate the optical proprieties of CIGS thin films.